2016
DOI: 10.1057/iga.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Who walks through the revolving door? Examining the lobbying activity of former members of Congress

Abstract: Abstract:Government watchdog groups and the government itself have shown concern about the "revolving door" of employees moving from Congress to private lobbying organizations. As of yet, the academic literature analyzing who becomes a revolving door lobbyist is small but growing. We contribute to this literature by examining which former members of Congress become lobbyists. We construct a dataset of all members of Congress who left the institution between 1976 and 2012, identifying those who go on to registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 17 publications
0
44
0
4
Order By: Relevance
“…This, again, is in stark contrast with the United States, where revolving door lobbyists start to work for the private sector in either the same year they leave or during the following one (Lazarus et al. ). This is further discussed below where we focus on how frequently the direct transition from the public to the private sector (and vice versa) occurs in the sample.…”
Section: A Career Path Analysis Of Eu Affairs Managersmentioning
confidence: 98%
See 2 more Smart Citations
“…This, again, is in stark contrast with the United States, where revolving door lobbyists start to work for the private sector in either the same year they leave or during the following one (Lazarus et al. ). This is further discussed below where we focus on how frequently the direct transition from the public to the private sector (and vice versa) occurs in the sample.…”
Section: A Career Path Analysis Of Eu Affairs Managersmentioning
confidence: 98%
“…Lazarus et al. () find that from 1976 to 2012 a quarter and almost a third, respectively, of members of the House of Representatives and Senators became lobbyists, with this trend increasing over time. Finally, Cain and Drutman () demonstrate that roughly a fifth of staff leaving Congress became lobbyists.…”
Section: A Political Economy Approach To Revolving Doorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selling (2015) quotes Lazarus et al (2013) as showing that after the US election in 2012 half of the outgoing House and 60 per cent of the members that left the Senate went on to register as lobbyists. In a more recent study by the same authors, Lazarus et al (2016) show that, based on a data set of all members of Congress who left the institution between 1976 and 2012, members of the House and the Senate are roughly equally likely to become lobbyists, but Republicans are more likely to become lobbyists than Democrats. In the Swedish studies reported in Garsten et al (2015), but also in Selling (2015) and Svallfors (2016), they find that amongst Swedish lobbyists (working in 2012) seven per cent come from a career in the Swedish parliament.…”
Section: The Relationship Between Politics and The Private Sector: Thmentioning
confidence: 97%
“…Similarly, if different types of former MCs select into lobbying differently, this too could bias the results. Lazarus, McKay, and Herbel () study the issue of what types of former MCs join lobbying firms, and show that there is meaningful variation in lobbying rates depending on institutional standing and, to a lesser extent, party. While we cannot entirely address the issue of sample selection in these descriptive regressions, the RDD approach used later in the article helps to address these concerns since it does not condition on people who became lobbyists…”
Section: Measuring Earnings From Lobbyingmentioning
confidence: 99%